2024
DOI: 10.11598/btb.1999.0.14.154
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Insects, Fungi and Organoleptic Characteristics in Stored Coffee Beans in Lampung

Abstract: A survey on postharvest handling and technology processing of coffee beans at farmer, trader and exporter levels was conducted in West Lampung and Tanggamus regencies of Lampung province during harvest time (July 1998). Interviews and sampling of coffee beans were carried out during the survey. The number of respondents at farmer, trader and exporter levels was 22, 20 and 4, respectively, while the number of samples collected from each level was 20. All samples were analyzed for moisture content, physical qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Lilia et al (2021) reported that the common postharvest fungus in coffee beans is A. niger. Dharmaputra et al (1999), who tested the level of fungal attack on coffee beans collected from traders in Lampung Province, also reported A. niger as the dominant fungus (46%). Furthermore, Yani (2008) stated that A. niger infects 100% of coffee beans during primary processing.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lilia et al (2021) reported that the common postharvest fungus in coffee beans is A. niger. Dharmaputra et al (1999), who tested the level of fungal attack on coffee beans collected from traders in Lampung Province, also reported A. niger as the dominant fungus (46%). Furthermore, Yani (2008) stated that A. niger infects 100% of coffee beans during primary processing.…”
Section: Discussionmentioning
confidence: 95%
“…An insect causes seeds with one hole and more than one hole. According to Dharmaputra et al (1999), during storage, coffee beans can be affected by insects, mites, microorganisms, and rodents; insect pests are considered to be the most significant cause of losses. However, when the observation was carried out, no insect pests were found.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee is one of the most popular beverages in the world (Romano et al 2014). Like many other stored products, post-harvest green coffee beans are vulnerable to damage from a variety of insect pests such as drugstore beetle ( Stegobium paniceum [L.]) (De Ong 1948), coffee bean weevil ( Araecerus fasciculatus [De Geer]) and maize weevil ( Sitophilus zeamais Motschulsky) (Dharmaputra et al 1999). A study reported 22, 2, and 8 species from Coleoptera, Lepidoptera, and other insect orders from coffee warehouses in Colombia, respectively.…”
Section: Introductionmentioning
confidence: 99%